Varieties of English: English as a mother tongue (The USA) (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation This article explores the diverse nature of American English as a mother tongue, highlighting its regional variations, vocabulary, and influences from immigrant communities. It emphasizes how American English reflects the cultural and historical heritage of the United States, showcasing its dynamic evolution over time.